The potential of alternatives to face-to-face consultation in general practice, and the impact on different patient groups: a mixed-methods case study - Helen Atherton; Heather Brant; Sue Ziebland; Annemieke Bikker; John Campbell; Andy Gibson; Brian McKinstry; Tania Porqueddu; Chris Salisbury (National Institute for Health Research, 2018)
Background: There is international interest in the potential role of different forms of communication technology to provide an alternative to face-to-face consultations in health care. There has been considerable rhetoric about the need for general practices to offer consultations by telephone, e-mail or internet video. However, little is understood about how, under what conditions, for which patients and in what ways these approaches may offer benefits to patients and practitioners in general practice. Objectives: Our objectives were to review existing evidence about alternatives to face-to-face consultation; conduct a scoping exercise to identify the ways in which general practices currently provide these alternatives; recruit eight general practices as case studies for focused ethnographic research, exploring how practice context, patient characteristics, type of technology and the purpose of the consultation interact to determine the impact of these alternatives; and synthesise the findings in order to develop a website resource about the implementation of alternatives to face-to-face consultations and a framework for subsequent evaluation. Design: Mixed-methods case study. Setting: General practices in England and Scotland with varied experience of implementing alternatives to face-to-face consultations. Participants: Patients and practice staff. Interventions: Alternatives to face-to-face consultations include telephone consultations, e-mail, e-consultations and internet video. Main outcome measures: How context influenced the implementation and impact of alternatives to the face-to-face consultation; the rationale for practices to introduce alternatives; the use of different forms of consultation by different patient groups; and the intended benefits/outcomes. Review methods: The conceptual review used an approach informed by realist review, a method for synthesising research evidence regarding complex interventions. Results: Alternatives to the face-to-face consultation are not in mainstream use in general practice, with low uptake in our case study practices. We identified the underlying rationales for the use of these alternatives and have shown that different stakeholders have different perspectives on what they hope to achieve through the use of alternatives to the face-to-face consultation. Through the observation of real-life use of different forms of alternative, we have a clearer understanding of how, under what circumstances and for which patients alternatives might have a range of intended benefits and potential unintended adverse consequences. We have also developed a framework for future evaluation. Limitations: The low uptake of alternatives to the face-to-face consultation means that our research participants might be deemed to be early adopters. The case study approach provides an in-depth examination of a small number of sites, each using alternatives in different ways. The findings are therefore hypothesis-generating, rather than hypothesis-testing. Conclusions: The current low uptake of alternatives, lack of clarity about purpose and limited evidence of benefit may be at odds with current policy, which encourages the use of alternatives. We have highlighted key issues for practices and policy-makers to consider and have made recommendations about priorities for further research to be conducted, before or alongside the future roll-out of alternatives to the face-to-face consultation, such as telephone consulting, e-consultation, e-mail and video consulting. Future work: We have synthesised our findings to develop a framework and recommendations about future evaluation of the use of alternatives to face-to-face consultations. Funding details: The National Institute for Health Research Health Services and Delivery Research programme.